Residents as Medical Student Mentors During the Obstetrics and Gynecology Clerkship. (October 2015) - Sobbing, Jackson; Duong, Jennifer; Dong, Frank; Grainger, David
Abstract : PURPOSE: To establish and evaluate a medical student mentoring program (MSMP) for medical students during their obstetrics and gynecology clerkship. BACKGROUND: Mentoring programs for medical students during core clerkships is novel for some institutions, including the University of Kansas School of Medicine-Wichita. Numerous potential benefits are possible. Identification and neutralization of potential barriers to implementation may lead to long term enthusiasm for and acceptance of the mentoring program. METHODS: One senior obstetrics and gynecology resident physician was assigned one or two medical students per 6-week rotation. Residents were given information regarding MSMP requirements, and randomly assigned to students. Students were provided MSMP information during clerkship orientation. Surveys were administered to students during orientation before meeting their residents and at the end of clerkship. Surveys were administered to residents during the last week of clerkships. RESULTS: Surveys were collected from 29 students. All students reported not having a MSMP available on other clerkships. Postclerkship, students indicated they would participate in the MSMP again (79.3%), felt other students would benefit from having a mentor on other clerkships (75.0%), and felt the MSMP was beneficial to their clerkship (81.5%). Students reported receiving educational (11, 44.0%) and clinical (21, 84.0%) instruction, personal development feedback (14, 56.0%), and career advice (6, 24.0%) from mentors. Mentors returned 16 feedback surveys; residents were not burdened by students (75.0%), and all mentors responded that they would participate in the MSMP again. DISCUSSION: Establishing a mentoring program for medical students during core clerkships is novel for the University of Kansas School of Medicine-Wichita, and may provide potential benefits and one-on-one instruction to medical students.